2023
DOI: 10.24815/cdj.v13i2.23536
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Leaflet Dan Video Animasi Sebagai Media Edukasi Dalam Meningkatkan Pengetahuan Terhadap Pentingnya Penggunaan Gigi Tiruan Pada Mahasiswa Poltekkes Jakarta Ii

Abstract: Kehilangan gigi yang tidak segera diganti dapat berpengaruh pada penurunan efisiensi kunyah, kelainan fungsi bicara, mengurangi penampilan dll. Pemanfaatan gigi tiruan sangatlah penting untuk menggantikan gigi geligi yang telah hilang karena pencabutan, namun tidak semua orang memahami dan menyadari penggunaannya. Penyuluhan kesehatan gigi memerlukan sarana berupa media edukasi untuk mempermudah penyampaian informasi. Penelitian ini bertujuan membandingkan penggunaan leaflet dan video animasi terhadap peningka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…A study of 32 students at the Health Polytechnic Ministry of Health Jakarta II also confirmed the impact of using animated videos as educational media in increasing students' knowledge. This study showed that animated video, as a media tool, is more meaningful than a leaflet (Prawesthi et al, 2021). This study identified areas of knowledge about COVID-19 and family resilience attitudes.…”
Section: Table 5: Analysis Of Differences In Knowledge About Covid-19mentioning
confidence: 81%
“…A study of 32 students at the Health Polytechnic Ministry of Health Jakarta II also confirmed the impact of using animated videos as educational media in increasing students' knowledge. This study showed that animated video, as a media tool, is more meaningful than a leaflet (Prawesthi et al, 2021). This study identified areas of knowledge about COVID-19 and family resilience attitudes.…”
Section: Table 5: Analysis Of Differences In Knowledge About Covid-19mentioning
confidence: 81%
“…The community service activities carried out in Dungaliyo Village are an effort to increase understanding and awareness and provide information and skills needed to prevent and manage hypertension by utilizing natural ingredients, namely butterfly pea flowers. Education about hypertension uses the socialization method in the form of presentations and the distribution of leaflets because it is proven to be more effective in increasing knowledge (Prawesthi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Selain itu, keteraturan informasi di dalam media leaflet juga mendukung retensi pembelajaran. Penelitian penelitian Prawesthi et al (2021), menemukan terdapat peningkatan pengetahuan setelah diberi perlakuan dengan Video animasi daripada hanya penggunaan media leaflet.…”
Section: Hasil Dan Pembahasanunclassified